Implementasi Program Sekolah Adiwiyata untuk Meningkatkan Karakter Peduli Lingkungan Siswa SDN Piyaman I - Erry Suntoro Sugiharto; Anwar Senen (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This study explores the implementation of the Adiwiyata Program at SDN Piyaman I, which differs from other schools through its routine of holding a morning assembly followed by litter collection from Monday to Thursday. The objectives were: (1) to describe how the program enhances students’ environmental care character, and (2) to analyze supporting factors and challenges in its implementation. Using a qualitative case study design, data were collected through interviews, observations, and documentation, then analyzed through data reduction, display, and conclusion drawing. The findings show that the program was successfully implemented, as students became accustomed to picking up litter after assemblies, significantly shaping their environmental care character. Supporting factors included the principal’s support, teachers’ active roles, the Adiwiyata team, student participation, and collaboration with parents, the community, and related institutions. Challenges such as limited awareness, lack of facilities, and uneven teacher understanding were addressed through persuasive approaches, socialization, and external collaboration.